اسلوبية التوظيف النفسي للأوامر العبادية في القرآن الكريم - Sabah Idan Hammoud (collage of education / university of Misan, 2021)
Each discourse aims, in its style and statement, to achieve the objectives of its creator, and in all its levels it has the intention of influencing the recipient to act upon it, and raise the potential of those aims It moves the recipient soul which is a group ((the forces latent in the human body, which is a complex of good emotions and evil impulses, and stable instincts, tendencies, emotions and desires that drive this physical body in its behavior and directions)). And she needs different stimuli to act with it and direct it towards Murad al-Qasid, who wants to be directed at it. Modern linguistic studies, especially stylistic research, have turned to psycho-linguistic research and the issuance of general laws to explain human behavior towards spoken linguistic phrases. The human soul needs, in its existence and at all its mental levels, internal stimuli that move it to patterns of actual or emotional behavior, which makes us adhere to the definition of the psychological connotation that was known as ((those features and signals that are reflected on the human soul, so that a specific response occurs in it, whether a) It was verbal or kinetic, voluntary or involuntary)) and the stylistics and coordination of the speech at the time of its creation and the place of its birth are important psychological influences. Therefore, this discourse should possess the stylistic ability to provoke